2015
DOI: 10.1111/anu.12289
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lutein/canthaxanthin ratio on the growth and pigmentation of large yellow croakerLarimichthys croceus

Abstract: This study was conducted to investigate the effects of dietary lutein/canthaxanthin ratio on the growth and skin coloration of large yellow croaker. Five carotenoids supplemented diets were formulated to contain 75/0, 50/25, 37.5/37.5, 25/50 and 0/75 mg kg À1 of lutein/canthaxanthin. The diet without carotenoids supplementation was used as the control. Fish of the similar size (13.83 AE 0.04 g) were fed with these experimental diets for 8 weeks in sea cages. Results showed that there were no significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
(39 reference statements)
3
12
1
Order By: Relevance
“…In the same sense with the current findings, dietary LTN at a dose of 75 mg kg −1 of feed provided higher yellowness and carotenoid content in the skin of the large yellow Croaker, Larimichthys croceus, [75]). Dietary LTN in powdered and nano forms significantly increased LTN levels in plasma, liver, eyes, and adipose tissue of guinea pigs [78].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the same sense with the current findings, dietary LTN at a dose of 75 mg kg −1 of feed provided higher yellowness and carotenoid content in the skin of the large yellow Croaker, Larimichthys croceus, [75]). Dietary LTN in powdered and nano forms significantly increased LTN levels in plasma, liver, eyes, and adipose tissue of guinea pigs [78].…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the skin, muscle, and whole-body content of carotenoids in fish fed LTN in combination with BS was significantly higher than the control. The determination of skin carotenoids is an accurate indicator for the quantitative fish skin pigmentation [23], whereas the coloration parameters were linearly related to the carotenoid content in the skin [75]. In fish, the biotransformation and degradation of LTN via oxidative and reductive pathways is not completely understood and differ from species to other [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…The astaxanthin concentration evaluated was within the margin recommended in the literature, which ranged from 36 to 80 mg/kg (Gouveia & Rema, 2005;Gouveia et al, 2003;Paripatananont et al, 1999). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016). Lutein inclusion levels are also showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…For goldfish, there are no studies evaluating the effects of diets supplemented with the combination of different carotenoids. For other ornamental fish species, the combination of carotenoid sources showed a synergistic effect by improving skin pigmentation (Wang et al, 2006;Yuangsoi, Jintasataporn, Areechon, & Tabthipwon, 2011) and health (Wang et al, 2006;Yi, Li, Xu, Zhang, & Mai, 2016). This response varies according to the species and source of carotenoid used.…”
Section: Discussionmentioning
confidence: 99%
“…Under intensive culture condition, farmed large yellow croaker is susceptible to lose its natural yellow colour. Several studies have shown that the skin colour of large yellow croaker was improved by dietary carotenoids and shrimp meal supplementations (Yi, Xu et al., ; Yi, Zhang, Xu, Li, Zhang & Mai ; Yi, Li, Xu, Zhang, et al., ; Yi, Li, Xu, Zhou, et al., ; Yi et al., ). Previous studies showed that increasing dietary vitamin E can improve the astaxanthin deposition in Atlantic salmon Salmo salar L (Bjerkeng, Hamre, Hatlen, & Wathne, ) or the canthaxanthin deposition in rainbow trout (Pozo, Lavety, & Love, ).…”
Section: Introductionmentioning
confidence: 99%